SELF-REPORTED READING STRATEGIES - B. Budiyono (Widya Mandala Surabaya Catholic University, 2015)
It is important for EFL readers to realize that they use certain strategies when they find difficulties in reading comprehension. These strategies have to be explored and selected for training for better comprehension. This exploration administered the MARSI reading questionnaire to identify university students’ reading strategies and their frequency of use. The global and support strategies turned to be the strategies of the medium level of use whereas the problem-solving strategies were at the high level of use. An interesting finding is that there was enough familiarity with the global and support strategies. The high-level of frequency of the problem-solving strategies indicate that there were a lot of difficulties in reading comprehension and the problem-solving strategies are worth training. To be more convincing, these findings would have to be supported by think-aloud protocols in real reading.